Photopatternable nano-composite (SU-8/ZnO) thin films for piezo-electric applications - Kandpal, Manoj; Sharan, Chandrashekhar; Poddar, Pankaj; Prashanthi, K.; Apte, Prakash R.; Rao, V. Ramgopal (Applied Physics Letters, 2012)
Photo-curable nanocomposite material was formulated by embedding ZnO nanoparticles into a SU-8 matrix and studied for its piezoelectric properties for low cost fabrication of self-powered nanodevices. The piezoelectric coefficient of ZnO nanoparticles was observed to be ranging between 15 and 23 pm/V, which is the highest reported. These experimental studies support the recent theoretical predictions where the piezoelectric coefficients in ZnO nanoparticles were found to be higher compared to the thin films because of the surface relaxation induced volume reductions in the nanometer scale. The photo-curable property of these polymer composite films is exploited to demonstrate fabrication of a micro-cantilever test structure. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748575]